A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 14 PEKANBARU IN COMPREHENDING HORTATORY EXPOSITION TEXT - Aradila Priando; Syofia Delfi; M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The purpose of this study is to find out the ability of the second year students of SMAN 14 Pekanbaru in comprehending hortatory exposition text. This research focuses on students’ comprehension about hortatory exposition text in terms of finding main ideas, factual information, finding meaning of difficult word, finding references, finding restatement, identifying the generic structure, language feature and social function .The data were collected using the multiple choice test. The test contained 40 items. The try out was conducted to check the validity and reliability of the test. Based on the result of the data analysis, it is found out that main idea (56.25) is classified as mediocre, the mean score of finding factual information is also (56.25) and classified as mediocre, the mean score of finding meaning of vocabulary (64.06) is classified as good. Meanwhile, the mean score of finding reference (64.38) is classified as good, the mean score of finding restatement (68.4) is classified as good. Meanwhile the mean score for the generic structure is (61.8) classified as good, the mean score for identifying language feature is (68.7) classified as good, and the last one is the result of the mean score of the identifying social function (63.7) is classified as good also. As whole, the researcher got the final result for the students’ ability in comprehending hortatory exposition text is (63.04), it means that the student ability is classified as good.Keywords : Study, Ability, Hortatory exposition text.